Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

a. 6 square root 2 - 5 square root 2

b. square root 11 + 3 square root 11


Sagot :

Step-by-step explanation:

Number A

= 6√2 - 5√2

= (6 - 5)√2

= √2

Number B

= √11 + 3√11

= (1 + 3)√11

= 4√11